2006
DOI: 10.1007/s00367-006-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-current control on sedimentation in the western Bellingshausen Sea, West Antarctica

Abstract: A set of single-and multi-channel seismic reflection profiles provide insights into the younger Cenozoic sedimentation history of the continental rise in the western Bellingshausen Sea, west and north of Peter I Island. This area has been strongly influenced by glacially controlled sediment supply from the continental shelf, interacting with a westward-flowing bottom current. From south to north, the seismic data show changes in the symmetry and structure of a prominent sediment depocentre. Its southernmost se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The influence of bottom currents on the distribution of sediments and structures of sediment deposits along the West Antarctic continental margin is well documented by several studies of contourite drifts at the Antarctic Peninsula margin [e.g., (Figure 2a). In addition to these, Scheuer et al [2006b] identified a channel related sediment drift at depocenter C in the western Bellingshausen Sea (Figure 2d). The development of such features seems to be related to the availability of contouritic detritus scavenged from continental slopes by frequently occurring turbidity currents.…”
Section: Influence Of Ocean Bottom Currentsmentioning
confidence: 90%
See 2 more Smart Citations
“…The influence of bottom currents on the distribution of sediments and structures of sediment deposits along the West Antarctic continental margin is well documented by several studies of contourite drifts at the Antarctic Peninsula margin [e.g., (Figure 2a). In addition to these, Scheuer et al [2006b] identified a channel related sediment drift at depocenter C in the western Bellingshausen Sea (Figure 2d). The development of such features seems to be related to the availability of contouritic detritus scavenged from continental slopes by frequently occurring turbidity currents.…”
Section: Influence Of Ocean Bottom Currentsmentioning
confidence: 90%
“…On the upper continental rise, depocenter C resembles a sediment drift, but distally it has the features of a simple channel levee Cunningham et al, 2002;Scheuer et al, 2006a]. According to Larter and Cunningham [1993] and Scheuer et al [2006b], the base of the drifts and channel levees indicate enhanced sediment supply to the continental rise due to advances of grounded ice to the continental shelf edge ( Figure 2d). …”
Section: Bellingshausen Seamentioning
confidence: 99%
See 1 more Smart Citation
“…There is widespread evidence for bottom current activity since~9.6 Ma in this area and in the Bellingshausen Sea further to the west (e.g. Nitsche et al, 2000;Rebesco et al, 2002;HernandezMolina et al, 2004;Hillenbrand and Ehrmann, 2005;Scheuer et al, 2006b;Uenzelmann-Neben, 2006). Uenzelmann-Neben and Gohl (2012) inferred bottom current activity as early as the Paleogene and the onset of major glaciations in West Antarctica at 14.1 Ma from seismic reflection profiles on the continental rise in the Amundsen Sea, but chronological control was poor.…”
Section: Palaeoenvironmental Settingmentioning
confidence: 99%
“…They used the age-depth model provided by DSDP Leg 35 Site 324 (Shipboard Scientific Party, 1976) for the upper 200 m of the sedimentary column comprising Pliocene/Pleistocene units and correlated this with observations on general changes in reflections characteristics. Variations in reflection characteristics for the deeper lying sequences were interpreted to represent modifications in the depositional regime and compared to observations from the Bellingshausen Sea (; Tucholke and Houtz, 1976;Tucholke et al, 1976b;Rebesco et al, 1996;Nitsche et al, 1997;Nitsche et al, 2000;Rebesco et al, 2002;Scheuer et al, 2006a;Scheuer et al, 2006b), which were tied to DSDP Leg 35 and ODP Leg 178 results, and the Ross Sea (De Santis et al, 1995;De Santis et al, 1999;Böhm et al, 2009), there correlated with results from DSDP Leg 28, to derive an age model. We make use of this stratigraphic model being aware of its poor chronological control but modify the names of the sedimentary units to distinguish them from the Ross Sea and Amundsen Sea shelf by adding the acronym ASR (Amundsen Sea rise).…”
Section: Seismostratigraphic Modelmentioning
confidence: 99%